Coefficient of repeatability of production in coconut palm - Siqueira, Edmar Ramos de (Pesquisa Agropecuaria Brasileira, 2014)
The coefficient of repeatability of coconut palm production was estimated in a population of 148 coconut plants in Sergipe State. The computed value for the coefficient of repeatability was r = 0.4545. This low value shows that a more rigorous method of selection must be adopted to improve the character of nut production. It also represented the maximum heritability value to that character, under the field conditions.